Evaluation of clinical and pathological response factors to neoadjuvant chemotherapy in breast cancer patients - Ferreira, Rayane; Kneubil, Maximiliano Cassilha; Brollo, Janaina; Tiago, Luiza Herdy Boechat Luz; Goulart, Karen Bazzo; Litvin, Isnard Elman; Ely, Mariana Roesch; Henriques, João Antonio Pêgas (Mastology, 2021)
Objectives: To evaluate breast cancer (BC) patients treated with neoadjuvant chemotherapy (NACT) and to analyze clinicopathological features correlating with pathological complete response (PCR) and survival outcomes. Methods: Observational, descriptive, and retrospective study. The medical records of BC patients who underwent NACT were reviewed and analyzed using the Statistical Package for the Social Sciences (SPSS), version 20.0. Results: Of the 176 BC patints who underwent NACT, 62 patients (35.2%) achieved PCR. The PCR rate was 22% (n = 2) for luminal A, 15% (n = 9) for luminal B/HER2-negative, 45.5% (n = 15) for luminal B/ HER2-positive, 50% (n = 14) for non-luminal/HER2-positive, and 47.8% (n = 22) for triple-negative (p = 0.01). Histological grade, estrogen receptor (ER) expression, progesterone receptor (PR) expression, and HER2 status were significantly associated with PCR (p = 0.022, p = 0.01, p = 0.01, and p = 0.02, respectively). The median follow-up was 35.9 months, the estimated 5-year disease-free survival (DFS) was 96.7% in the PCR group and 83.2% in the non-PCR group (p = 0.05). The estimated 5-year overall survival (OS) was 95.5% in the PCR group and 69.1% in the non-PCR group (p = 0.017). Overall, 11 patients (6.25%) presented with locoregional recurrence (LRR), one (1.6%) in the PCR group and 10 (8.8%) in the non-PCR group (p = 0.10). Conclusion: We observed higher PCR rates in triple-negative and HER2-positive molecular subtypes. DFS and OS were significantly better in patients who achieved PCR, regardless of clinicopathological features. We also observed lower rates of LRR in the population that reached PCR.